PENINGKATAN KOMPETENSI MENGAJAR GURU MELALUI PELAKSANAAN KELOMPOK KERJA GURU DI SMP NEGERI 5 DUMAI TAHUN 2022 - HUSNI HUSNI (JURNAL ILMIAH KOHESI, 2022)
This research was conducted at SMP Negeri 5 Dumai in the even semester of the 2021/2022 learning year. This research started from January 2022 to March 2022. The subject of this school action research is the teachers of SMP Negeri 5 Dumai, totaling 15 people. The form of this research is School Action Research (PTS). School action research aims to improve teacher competence at SMP Negeri 5 Dumai by implementing teacher working groups so as to improve teaching competence in the learning process. The results of this school action research show that the implementation of teachers' working groups can improve the teaching competence of teachers at SMP Negeri 5 Dumai in 2022. The observation result of teachers' teaching competence before the implementation of teachers' working group is 37.8% with less category. The results of observations of teacher competence through the implementation of teachers' working groups teaching cycle I was 68.9% with a sufficient category and in cycle II reached 80.6% with a good category.